U-PB (SHRIMP II) AGE OF ZIRCONS FROM ASH BEDS OF THE CHERNOKAMEN FORMATION, VENDIAN SYLVITSA GROUP (CENTRAL URALS) - Ronkin Yu.L.; Maslov A.V.; Mizens G.A.; Krupenin M.T.; Petrov G.A.; Lepikhina O.P.; Kornilova A.Yu.; Grazhdankin D.V.; Matukov D.I. (My University, 2006)
The Serebryanka and Sylvitsa groups on the western slope of the Urals characterize the Vendian section of the eastern folded framework of the East European Platform [1]. They are conspicuous against the background of the coeval platformal sequences by their relatively complete sedimentary record, sufficiently good outcrops, and opportunities for detailed sedimentological study both along and across the regional paleoslope. The tillite units serve as key elements of the stratigraphic framework of the Serebryanka Group.
Keywords: Serebryanka; Sylvitsa; Urals; Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский